Violence, custom and law : the Anglo-Scottish border lands in the later Middle Ages - Neville, Cynthia J. (Edinburgh University Press, 1998)
Long-standing hostility between Scotland and England affected the pattern of criminal activity in the Anglo-Scottish Border lands. This is an account of how the area created and refined a new system of law to deal with conflicts in the Middle Ages.